2014
DOI: 10.1186/1550-2783-11-28
|View full text |Cite
|
Sign up to set email alerts
|

Oral adenosine-5’-triphosphate (ATP) administration increases blood flow following exercise in animals and humans

Abstract: IntroductionExtracellular adenosine triphosphate (ATP) stimulates vasodilation by binding to endothelial ATP-selective P2Y2 receptors; a phenomenon, which is posited to be accelerated during exercise. Herein, we used a rat model to examine how different dosages of acute oral ATP administration affected the femoral blood flow response prior to, during, and after an exercise bout. In addition, we performed a single dose chronic administration pilot study in resistance trained athletes.MethodsAnimal study: Male W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
(32 reference statements)
0
22
0
Order By: Relevance
“…ATP and adenosine have been known to induce vasodilation following release from the erythrocytes via production of nitric oxide and prostacyclin (Nyberg et al 2010;Sprague et al 2011), and it has been recently demonstrated that exogenous ATP supplementation is capable of increasing exercise-induced blood flow (Jäger et al 2014). Improved blood flow may increase nutrient delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP and adenosine have been known to induce vasodilation following release from the erythrocytes via production of nitric oxide and prostacyclin (Nyberg et al 2010;Sprague et al 2011), and it has been recently demonstrated that exogenous ATP supplementation is capable of increasing exercise-induced blood flow (Jäger et al 2014). Improved blood flow may increase nutrient delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, more thorough research is required before considering this as a viable mechanism because of the fact that previously enhanced intramuscular ATP levels have only been examined in 1 resting subject (Reyes-Izquierdo et al 2014). Yet, the blend of ancient peat and apple extracts may be advantageous to direct ATP supplementation for these reasons, as direct ATP supplementation may only exert extracellular effects because of rapid degradation to its metabolites (Hochachka et al 1991;Gorman et al 2007;Mortensen et al 2011;Jäger et al 2014). The present study was limited by not measuring ATP levels either in whole-blood or muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…ATP and its metabolite adenosine can act through purinergic receptors in endothelial smooth muscle resulting in vasodilation and increased blood flow (Ellis et al 2012). Oral ATP administration has been shown to increased blood flow and improve muscular function (Jäger et al 2014), and are currently registered in France for the treatment of low back pain of muscular origin (Bannwarth et al 2005). In addition, ATP can trigger signalling cascades for metabolic adaptation related to neuromuscular activity (phosphorylation of ERK1/2) (May et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oral administration of ATP in the form of a disodium salt can increase blood flow in animal and human studies, which could be effective in treating depressive symptoms (Jäger et al, 2014). Furthermore, a study using a mouse model of depression showed that low levels of brain ATP was a susceptibility factor for chronic social defeat and that administration of ATP induced a rapidantidepressant-like effect (Cao et al, 2013).…”
Section: Candidate Drug Analysismentioning
confidence: 99%